2021
DOI: 10.1186/s12889-021-10313-x
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of functional health literacy to improve chronic airway disease outcomes

Abstract: Background Current conceptual models of health literacy (HL) illustrate the link between HL and health outcomes. However, these models fail to recognize and integrate certain elements of disease management, health system factors, and socio-demographic factors into their framework. This article outlines the development of Chronic Airway Disease (CAD) Management and Health Literacy (CADMaHL) conceptual model that integrates the aforementioned elements and factors into a single framework. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…We found that patient involvement in prior HL tool-development processes was rare [33,48,49,51]. Our participants also mentioned, from their experience, that patients' voices were often missing when developing educational interventions, particularly as related to disease-management practices [45,60,69].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We found that patient involvement in prior HL tool-development processes was rare [33,48,49,51]. Our participants also mentioned, from their experience, that patients' voices were often missing when developing educational interventions, particularly as related to disease-management practices [45,60,69].…”
Section: Discussionmentioning
confidence: 93%
“…A validity-driven approach [48] was employed in the development of the VAHLT. We applied the five-domain HL definition suggested by CCHL [2], which is widely used in the HL field [38].…”
Section: Theoretical Grounding and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Accurate measurement of evaluation skills could help to identify the differences between patients’ expectations and their perceptions of the services and information received [ 61 ]. This evaluation skill component of HL is understudied, particularly in AD [ 68 , 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between ethnicity, socio-economic status, and digital/health literacy are multifaceted and complex [ 3 , 4 ] but the data generally demonstrate that significant disparities exist that disproportionately affect minority and lower socio-economic groups [5] , [6] , [7] . While one can argue these challenges are not exclusive to any single specialty[ 8 , 9 ], CF teams would do well to consider how best to tailor systems to improve outcomes for people with CF [10] .…”
mentioning
confidence: 99%